Synthetic Lethality between DNA Polymerase Epsilon and RTEL1 in Metazoan DNA Replication - Roberto Bellelli; Jillian Youds; Valerie Borel; Jennifer Svendsen; Visnja Pavicic-Kaltenbrunner; Simon J. Boulton (Cell Reports, 2020)
Summary: Genome stability requires coordination of DNA replication origin activation and replication fork progression. RTEL1 is a regulator of homologous recombination (HR) implicated in meiotic cross-over control and DNA repair in C. elegans. Through a genome-wide synthetic lethal screen, we uncovered an essential genetic interaction between RTEL1 and DNA polymerase (Pol) epsilon. Loss of POLE4, an accessory subunit of Pol epsilon, has no overt phenotype in worms. In contrast, the combined loss of POLE-4 and RTEL-1 results in embryonic lethality, accumulation of HR intermediates, genome instability, and cessation of DNA replication. Similarly, loss of Rtel1 in Pole4−/− mouse cells inhibits cellular proliferation, which is associated with persistent HR intermediates and incomplete DNA replication. We propose that RTEL1 facilitates genome-wide fork progression through its ability to metabolize DNA secondary structures that form during DNA replication. Loss of this function becomes incompatible with cell survival under conditions of reduced origin activation, such as Pol epsilon hypomorphy.